Analisis Manfaat Pojok Baca untuk Menanamkan Minat Baca Siswa Kelas IV SD Negeri Ringinsari - Hamdan Kasim; Sabarudin Sabarudin; Syamsul Bahri Mamonto; Friska Mokodongan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to analyze the benefits of reading corners in fostering a programmed interest in reading at SDN Ringinsari. The research method used is qualitative with a descriptive approach. Data collection techniques using interviews and observation. Data analysis techniques were carried out descriptively by looking at the results of interviews and observations. Based on the results of data analysis, it can be concluded that the use of a reading corner for fourth grade students at SD Negeri Ringisari is that there is a reading corner in the classroom to bring knowledge sources closer to students and to foster basic literacy. Increasing the frequency of reading students because at will they can read books in the reading corner, the use of the reading corner in the learning process is done 15 minutes before learning begins and when it is empty, the class reading corner is neatly arranged at the beginning of learning until the end of learning to make it easier for students to find the book you want to read.